Ответы и объяснения

2011-09-27T13:54:02+00:00

у= 6 -2х

2х (6-2х)=5

12х - 4 х в 2= 5

- 4х в 2+12х - 5 =0

д= 12 в 2- 4*(-4)*(-5)= 64

х1= 0,5 х2= 2,5

у1= 6-2*0,5=5

у2= 6- 2*2,5=1

Ответ: (0,5;5)(2,5;1) 

2011-09-27T14:09:05+00:00

Первое

2х=5/у

5/у+у=6

5+у2=6у

у2-6у+5=0

D=36-20=16

Первый корень у1=(6-4)/2=1

Второй корень у2=(6+4)/2=5

2х=5/1=5 х=2,5 при у=1

2х=5/5=1 х=0,5 при у=5

 

Второе

х2+2=у

2х+х2+2=2

2х+х2=0

х*(2+х)=0

Первый х=0, второй х=-2

Значит при х=0, у=2, а при х=-2, у=6

 

Третье

х=3-у

(3-у)2+у2=29

9-6у+у2+у2=29

2у2-6у-20=0

у2-3у+10=0

Первый корень равен у1=-2, второй у2=5

При у=-2, х=5

При у=5, х=-2